Pelatihan Troubleshooting Kerusakan Sepeda Motor Di Desa Pelutan Kabupaten Purworejo - Widiyatmoko Widiyatmoko; Mike Elly Anitasari; Aci Primartadi; Widodo Widodo (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The community service carried out in Pelutan village aims to train participants to have the knowledge and information to do troubleshooting or detect motorbike damage. To achieve this goal, training was carried out using the counseling method by delivering material on troubleshooting and how to handle motorcycle damage. The activity was attended by 18 participants. Methods of implementing activities include: preparation, implementation, and reflection. Preparation is carried out by analyzing the problems and needs of the training participants. The implementation of the activity is carried out using the lecture method (question and answer) followed by a reflection stage. The end result of the community service activity is that participants can troubleshoot motorcycle damage and know how to handle it. The results of the analysis of the activity reflection questionnaire are as follows: 1) Understanding of troubleshooting material scores 92 %; 2) The benefits of the activity material presented with a score of 90%; 3) The level of pleasure or satisfaction of participants in the activity gets a score of 80%. Based on the reflection data of community service activities, it was concluded that the implementation of community service received a good response, hoping for further follow-up.